Enhancing the capacitance and active surface utilization of supercapacitor electrode by graphene nanoplatelets. (20th May 2015) - Pullini, D.; Siong, V.; Tamvakos, D.; Lobato Ortega, B.; Sgroi, M.F.; Veca, A.; Glanz, C.; Kolaric, I.; Pruna, A.
Abstract: The potential application of graphene nanoplatelets as electrode material in supercapacitors with high energy density was investigated. The electrode were prepared with commercially available graphene nanoplatelets before and after being functionalized with MnO2 particles, and with those electrochemically exfoliated from graphite. The morphology, structure and the specific surface area properties of each material were analyzed prior to test the electrochemical performance of the corresponding electrodes under the design constraints of real devices by cyclic-voltammetry (CV) and charge/discharge (CD) measurements. The results indicated that graphene nanoplatelets show potential in replacing activated carbon for the fabrication of supercapacitors with high energy density, while the efficient usage of active surfaces available of the electrode material should be considered.